From Single to Multiplayers: A History of Digital Games (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2014)
The purpose of this essay is to present a historical approach about the innovative transformations wrought in the realm of digital games. It is intended to highlight and discuss how conceptual innovations, evolution of technological devices and technical-artistic developments prevented the emergence of various shapes, variations and game genres and modes of play, finally giving rise to so-called multiplayer games. It is expected, therefore, contribute to the understanding of this cultural manifestation of contemporary leisure.